To solve this system of equations using substitution, we'll start by solving one of the equations for one variable and then substituting that expression into the other equation.
From the second equation, we can solve for x:
x - 5y = -20
x = 5y - 20
Now we'll substitute this expression for x into the first equation:
-4(5y - 20) + 6y = 38
-20y + 80 + 6y = 38
-14y + 80 = 38
-14y = -42
y = 3
Now that we have found the value of y, we can substitute it back into the expression for x:
x = 5(3) - 20
x = 15 - 20
x = -5
Therefore, the solution to the system of equations is x = -5 and y = 3.
Solving equations using substitution Quick check
Solve the system of equations . - 4x + 6y = 38; x - 5y = - 20 (1 point)
1 answer